Melanonychia associated with subungual follicular inclusions: report of three cases, - Marina Câmara de Oliveira; Carlos Baptista Barcaui; Elisa de Oliveira Barcaui; Juan Piñeiro-Maceira (Sociedade Brasileira de Dermatologia, 2020)
Abstract Melanonychia is the change in the coloration of the nail plate resulting from the deposition of melanin. Among its causes are melanocytic hyperplasia, melanocytic activation and nail melanoma. Subungual follicular inclusions are histological findings of unknown etiology, possibly related to trauma. We present three cases of melanonychia of different etiologies with subungual follicular inclusions, an association that has not been well described and with an indefinite pathogenesis.